Radio-echo sounding and ice volume estimates of western Nordenskiöld Land glaciers, Svalbard - Martín Español, Alba; Vasilenko, Evgeniy; Navarro Valero, Francisco José; Otero García, Jaime; Lapazaran Izargain, Javier Jesús; Lavrentiev, Nikita; Macheret, Yu; Machío, F. (Annals of Glaciology, 2013)
As part of ongoing work to obtain a reliable estimate of the total ice volume of Svalbard glaciers and their potential contribution to sea-level rise, we present here volume calculations, with detailed error estimates, for ten glaciers on western Nordenskiöld Land, central Spitsbergen, Svalbard. The volume estimates are based upon a dense net of GPR-retrieved ice thickness data collected over several field campaigns spanning the period 1999-2012. On the basis of the pattern of scattering in theradargrams, we also analyse the hydrothermal structure of these glaciers.